InaRISK Personal for Disaster Risk Literacy: A Content Analysis of Indonesia's Mobile Education Platform - Susilastuti; Maarif, Syamsul; Kusuma; Kurniadi, Anwar (Cita konsultindo, 2025)
Digital innovation reshapes disaster preparedness education, with mobile platforms offering accessible learning opportunities. This study examines InaRISK Personal, Indonesia's government-developed mobile disaster education application, addressing the research gap in evaluating digital disaster preparedness tools in developing countries. Using descriptive qualitative content analysis combined with systematic literature review, we assessed the application against established disaster education frameworks (Petal et al., 2008; Paton & Johnston, 2017). Analysis reveals InaRISK Personal provides localized risk assessments, real-time hazard mapping, and personalized mitigation recommendations across four disaster phases. Despite 399,000 cumulative downloads by December 2024, active monthly users declined 18.85%, indicating critical retention challenges. Key barriers include limited digital literacy in Indonesia's context, weak curriculum integration, and absence of gamification features. This study contributes the first comprehensive content analysis of a government-developed disaster education app in Indonesia's high-risk context, providing empirical evidence of the retention paradox, where initial adoption does not guarantee sustained engagement. Findings suggest enhancing teacher training, embedding platforms within curricula, implementing engagement strategies, and strengthening digital literacy programs are critical for maximizing mobile-based disaster preparedness education effectiveness in disaster-prone developing countries.